1998
DOI: 10.1016/s0735-1097(97)00542-1
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral Vascular Endothelial Dysfunction in Patients With Angina Pectoris and Normal Coronary Arteriograms

Abstract: These findings suggest that endothelial dysfunction in microvascular angina is a generalized process that also involves the peripheral conduit arteries and is similar to that observed in atherosclerotic disease. IMT could be helpful in discriminating patients with microvascular angina and atherosclerotic coronary artery disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
55
0
3

Year Published

1999
1999
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(66 citation statements)
references
References 28 publications
8
55
0
3
Order By: Relevance
“…Because this reduction occurred, however, together with and in relation to an increase in arterial wall thickness, an alteration in arterial wall structure is presumably involved. This alteration could originate from the reduced nitric oxide secretion that can be seen in diabetes [39], because firstly nitric oxide has been shown to oppose proliferation of vessel wall tissue in vitro [40] and secondly endothelial function has been found to be inversely related to carotid artery wall thickness both in studies of animals and humans in vivo [41,42]. It could, however, also be due to the insulin given exogeneously because insulin is known to be a growing factor for vascular wall tissues [43].…”
Section: Discussionmentioning
confidence: 99%
“…Because this reduction occurred, however, together with and in relation to an increase in arterial wall thickness, an alteration in arterial wall structure is presumably involved. This alteration could originate from the reduced nitric oxide secretion that can be seen in diabetes [39], because firstly nitric oxide has been shown to oppose proliferation of vessel wall tissue in vitro [40] and secondly endothelial function has been found to be inversely related to carotid artery wall thickness both in studies of animals and humans in vivo [41,42]. It could, however, also be due to the insulin given exogeneously because insulin is known to be a growing factor for vascular wall tissues [43].…”
Section: Discussionmentioning
confidence: 99%
“…However, MFR did not relate to endothelial dysfunction in isolated subcutaneous resistance arteries as measured by acetylcholine-induced vasodilatation. Impaired FMD has been demonstrated in patients with microvascular angina and coronary artery disease, 11 and has been related to coronary endothelial dysfunction in patients evaluated for coronary artery disease. 37 Our results extend these findings to hypertensive patients without coronary heart disease, but with LV hypertrophy on electrocardiogram.…”
Section: Vasodilatory Dysfunctionmentioning
confidence: 99%
“…medium-sized conduit arteries 8 and in resistance arteries. 9,10 Nonhypertensive patients with symptoms of angina pectoris, but with normal coronary angiograms, have decreased flow-mediated dilatation (FMD) in the brachial artery during reactive hyperaemia, 11 as well as increased minimal forearm vascular resistance (FVR), 12 suggesting parallel vascular dysfunction in the coronary and peripheral vasculature. This parallel vascular dysfunction has also been identified by Leschke et al, 13 who found increased minimal FVR in hypertensive patients with reduced MFR.…”
Section: Introductionmentioning
confidence: 99%
“…Microvascular dysfunction appears to be part of a systemic process 33,34) . The functional capacity of the myocardial microcirculation may be assessed by CFR, and GFR may in part reflect and rely on the integrity of the renal microvascular bed.…”
Section: Discussionmentioning
confidence: 99%